ATTACHMENT SECURITY AND PSYCHOLOGICAL HEALTH IN ADULT CHILD CAREGIVERS AND PARENTS WITH DEMENTIA. (16th November 2018) - Monin, J; Feeney, B; Schulz, R
Abstract: Attachment theory states that attachment security, providing and receiving communication of safety and emotional support, is one of the most fundamental needs in parent-child dyads across the lifespan. Having greater attachment security protects psychological health, especially in times of crisis. This study examined the association between attachment security and psychological health in 45 adult child caregivers and their parent with early stage Alzheimer's disease and related dementias. Both dyad members were interviewed, assessing their attachment styles, depressive symptoms, and quality of life. Results show that the caregiver's avoidant and anxious attachment (attachment insecurity) were significantly positively associated with greater depressive symptoms (anxiety: β=.45, p<.01; avoidance: β=.53, p<.001). The parent's anxious attachment was associated with worse quality of life (β=-.43, p<.05). Results remained when controlling for cognitive and physical functioning and socio-demographics. Findings suggest that attachment security may protect the psychological health of adult child caregivers and their parents with ADRD.